Persepsi Masyarakat Nelayan Terhadap Pendidikan Formal Anak - Wasti Alokamai (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2023)
The purpose of this study was to determine fishermen’s perceptions about the importance of children’s formal education, and the factors that influence fishermen’s perceptions. The data were collected by observation, interviews, and documentation. The subject of this study was parents and children who continue their education and those who are not. The study showed that there are still parents who think that education is not important. It is a waste of time, money, energy and thought. Education is considered a way to get a job, even though it can also be by helping parents to work. Besides, there are also some parents who think that education is very important for their children’s future. The factors that influence the fishermen’s perception are parental education, inadequate economics, environment and parent’s motivation.